1982
DOI: 10.1520/jfs11487j
|View full text |Cite
|
Sign up to set email alerts
|

Application of Proton-Induced X-Ray Emission Technique to Gunshot Residue Analyses

Abstract: The proton-induced X-ray emission (PIXE) technique was applied to the identification and analysis of gunshot residues. Studies were made of the type of bullet and bullet hole identification, firearm discharge element profiles, the effect of various target backings, and hand swabbings. The discussion of the results reviews the sensitivity of the PIXE technique, its nondestructive nature, and its role in determining the distance from the gun to the victim and identifying the type of bullet used and whether a wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The former provides quantitative and elemental information [ 13 , 15 , 42 ], whereas AFM allows a very high-resolution picture of the GSR particles at nanoscale dimensions [ 43 ]. On the other hand, PIXE is a technique that employs a beam of high-energy particles for elemental analysis [ 44 ], and NAA is a highly sensitive approach that focuses on the nucleus of the atoms present in the elements of the sample with quantitative capabilities [ 16 , 45 ]. Moreover, mass spectrometry with inductively coupled plasma (ICP-MS) also proved valuable for IGSR particles analysis [ 14 , 16 ].…”
Section: Main Components Of Gunpowder and Gunshot Residuementioning
confidence: 99%
“…The former provides quantitative and elemental information [ 13 , 15 , 42 ], whereas AFM allows a very high-resolution picture of the GSR particles at nanoscale dimensions [ 43 ]. On the other hand, PIXE is a technique that employs a beam of high-energy particles for elemental analysis [ 44 ], and NAA is a highly sensitive approach that focuses on the nucleus of the atoms present in the elements of the sample with quantitative capabilities [ 16 , 45 ]. Moreover, mass spectrometry with inductively coupled plasma (ICP-MS) also proved valuable for IGSR particles analysis [ 14 , 16 ].…”
Section: Main Components Of Gunpowder and Gunshot Residuementioning
confidence: 99%
“…In 1982, the use of inductively coupled plasma optical emission spectrometry (ICP/OES) was reported to identify Ba (Sen et al, 1982). This technique showed greater precision and accuracy than AAS for the determination of Ba in GSR, besides not suffering interference due to the presence of grease, dirt, or blood.…”
Section: Some Background: Conventional Gsr Characterizationmentioning
confidence: 99%
“…Studies of firearm discharge element profiles around bullet holes indicated that the firing distance could be estimated by this technique. Furthermore, studies of hand swabs from, firers showed that the high sensitivity of this procedure (0.1-1 ng) can help screen out suspects who have not handled a weapon (371). Another approach examined was anodic stripping voltammetry.…”
Section: Forensic Biochemistrymentioning
confidence: 99%